2016
DOI: 10.1186/s12968-016-0310-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial deformation in children by cardiovascular magnetic resonance feature tracking: determination of reference values for left ventricular strain and strain rate

Abstract: BackgroundThe objective assessment of global and regional cardiac function in children has shown to be clinically relevant but is challenging to conduct. Cardiovascular magnetic resonance (CMR) has emerged as a valuable diagnostic modality especially in patients with cardiomyopathy or congenital heart disease. However, data on the normal cardiac deformation in children assessed by CMR is lacking at present. Thus, the aim of this study was to provide reference values for cardiac strain and strain rate in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 35 publications
4
43
1
1
Order By: Relevance
“…In our study, the 32 control group volunteers showed strain values within the reference range. In another study by André et al [23] that used parabolic regression equations, no sex-related differences were found in the assessed strain values in children and adolescents. Our study showed significant age differences between the patient group and control group.…”
Section: Discussionmentioning
confidence: 87%
“…In our study, the 32 control group volunteers showed strain values within the reference range. In another study by André et al [23] that used parabolic regression equations, no sex-related differences were found in the assessed strain values in children and adolescents. Our study showed significant age differences between the patient group and control group.…”
Section: Discussionmentioning
confidence: 87%
“…Cardiovascular MRI is routinely used as the gold standard imaging technique for the assessment and follow‐up of specific groups of CHDs (eg, conotruncal abnormalities, right‐sided lesions, great vessels anomalies) . In such anomalies, to find measurements different from normal (eg, ascending aorta and pulmonary arteries in tetralogy of Fallot [TOF]) is almost the rule . In this setting it is important to understand not only how much a given measurement is distant from normal but also if this measure is or not similar to those of other children with the same defect.…”
Section: Discussionmentioning
confidence: 99%
“…1 In such anomalies, to find measurements different from normal (eg, ascending aorta and pulmonary arteries in tetralogy of Fallot [TOF]) is almost the rule. 1,[18][19][20][21][22][23] In this setting it is important to understand not only how much a given measurement is distant from normal but also if this measure is or not similar to those of other children with the same defect. Thus, a few recent studies [18][19][20][21][22][23] tried to derive expected abnormal cardiovascular MRI values in specific CHD with attention to repaired TOF, which is one of the most frequent indications for cardiovascular MRI examinations in the pediatric age and in young adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations